FORMULATION AND DEVELOPMENT OF EFAVIRENZ TABLETS BY PAPER TECHNIQUE USING CO-SOLVENCY METHOD - SUBRAHMANYESWARI, CH. DHANA; PRASANTH, Y.; RUBEEN, SAMEEDA (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present study is to formulate and development of efavirenz tablets by paper technique using the co-solvency method, the drug is antiviral drug used for the treatment of HIV. Methods: In this 7 formulation (F1-F7) were prepared by using different tissue papers like kitchen roll paper, hand kercheif paper, facial tissue paper, with different weights. The prepared tablets were evaluated for hardness, friability, thickness, content uniformity, disintegration time and in vitro dissolution study. Results: Among all the formulations, F2 (kicthen roll paper with weight 250 mg) was consired to be the best formulation, which release up to 98.02% drug in 3 h. The results of stability studies of formulation F2 after a period of 2 mo indicated that the formulation was stable. Conclusion: It was concluted that a paper tablet of efavirenz shows better results and it does not contain any excipient and increase the dissolution rate.